2006
DOI: 10.1039/b516086c
|View full text |Cite
|
Sign up to set email alerts
|

Platinum–acetylide polymer based solar cells: involvement of the triplet state for energy conversion

Abstract: Relatively efficient photovoltaic devices were fabricated using blends of a phosphorescent platinum-acetylide polymer and a fullerene (PCBM); involvement of the triplet excited state of the platinum-acetylide polymer in photoinduced charge transfer is believed to contribute to the device efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
195
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(197 citation statements)
references
References 17 publications
1
195
0
1
Order By: Relevance
“…In contrast, metallated conjugated polymers have rarely been tested as donor materials in bulk-heterojunction solar cells. [86,87] In early reports, power-conversion efficiencies significantly below 1% were published. Recently, Wong et al [70] demonstrated highly efficient bulk-heterojunction solar cells using polymer 6 (Fig.…”
Section: Metallated Conjugated Polymersmentioning
confidence: 99%
“…In contrast, metallated conjugated polymers have rarely been tested as donor materials in bulk-heterojunction solar cells. [86,87] In early reports, power-conversion efficiencies significantly below 1% were published. Recently, Wong et al [70] demonstrated highly efficient bulk-heterojunction solar cells using polymer 6 (Fig.…”
Section: Metallated Conjugated Polymersmentioning
confidence: 99%
“…It is known that the spinorbit coupling flips the singlet spin configuration to triplet and vice versa and hence facilitates ISC [6,8,13]. ISC from a singlet excited state to a triplet excited state has been studied theoretically [14][15][16] and as well as experimentally [11,12]. Theoretical models have so far been limited to either numerical calculation of ISC rates [14][15][16] or estimation of the spin-orbit interaction transition matrix element [17].…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of iridium (Ir) and platinum (Pt) into the active layer of OSCs results in the phosphorescent sensitizer, fac-tris(2-phenylpyridine) iridium [Ir(ppy)3] [1,10] and platinum-acetylide [p-PtTh] [11] and has been found Intersystem crossing rate from singlet excited state to triplet excited state of an organic molecule has been derived using exciton-spin-orbit-molecular vibration interaction as a perturbation operator. Incorporation of heavy metal atom enhances the spin-orbit interaction and hence the intersystem crossing rate because it depends on the square of the heaviest atomic number.…”
Section: Introductionmentioning
confidence: 99%
“…[8,17] A free e-h pair does not have a distinct singlet or triplet spin character; [14] however, prior to dissociation, a CT exciton will still be spin correlated to the singlet or triplet state. In Equations (12) and (13) we have derived spin-dependent recombination rate constants from which we can calculate how, prior to charge separation of dissociated exciton, the charges can still be drawn back to their original excitonic state and possibly decay to the ground state.…”
mentioning
confidence: 99%